2019
DOI: 10.1097/cnq.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Acute Management of Hypertension Following Intracerebral Hemorrhage

Abstract: Intracerebral hemorrhage (ICH) is responsible for approximately 15% of strokes annually in the United States, with nearly 1 in 3 of these patients dying without ever leaving the hospital. Because this disproportionate mortality risk has been stagnant for nearly 3 decades, a main area of research has been focused on the optimal strategies to reduce mortality and improve functional outcomes. The acute hypertensive response following ICH has been shown to facilitate ICH expansion and is a strong predictor of mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 103 publications
0
9
0
2
Order By: Relevance
“…As one of the major life-threatening human pathologies, intracerebral haemorrhage (ICH) is the aetiology underpinning approximately 8–15% of cerebrovascular accidents in the United States each year (Unnithan and Mehta 2021 ). Worldwide epidemiological statistics have indicated that 24.6 individuals per 100,000 experience ICH; these figures are even greater in Asian communities (Weimar and Kleine-Borgman 2017 ; Haller et al 2019 ). The rising incidence of ICH is thus an area of global concern (Sedova et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As one of the major life-threatening human pathologies, intracerebral haemorrhage (ICH) is the aetiology underpinning approximately 8–15% of cerebrovascular accidents in the United States each year (Unnithan and Mehta 2021 ). Worldwide epidemiological statistics have indicated that 24.6 individuals per 100,000 experience ICH; these figures are even greater in Asian communities (Weimar and Kleine-Borgman 2017 ; Haller et al 2019 ). The rising incidence of ICH is thus an area of global concern (Sedova et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is, to our knowledge, the first case to report a COVID-19 patient with a complication of cerebral hemorrhage. Hypertension is the most common cause of cerebral hemorrhage [5]. Coagulopathy remains a common cause of cerebral hemorrhage [6].…”
mentioning
confidence: 99%
“…The solution-focused approach is an intervention model of clinical central psychotherapy, which has gradually developed into an intervention model in nursing rehabilitation after clinical practice [ 17 20 ]. This model respects individuals and improves patients' subjective initiative during rehabilitation by constantly tapping into their own resources and potential.…”
Section: Discussionmentioning
confidence: 99%